Ensuring Equality in Higher Education Partnerships Involving Unequal Universities in Divergent Contexts - Hagenmeier, Cornelius (International Higher Education, 2015)
This contribution investigates whether international higher education partnerships, as presently constructed, are truly equal. The inquiry is inspired by the inequality evident in the divergent profile of universities collaborating in some higher education partnerships. The article proposes a higher education partnership model which is based on the notion of substantive equality.